2017
DOI: 10.1016/j.actamat.2016.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Probing the densification mechanisms during flash sintering of ZnO

Abstract: a b s t r a c tThe eutectic temperature and composition of the TiO 2 -CuO system were carefully measured to be 1010 ± 10 C and 83CuO:17TiO 2 , respectively. Subsequently, a TiO 2 -CuO phase diagram was computed, representing a correction and major improvement from the phase diagram available in literature. Dilatometry measurements and isothermal sintering experiments unequivocally demonstrated the activated (enhanced) sintering of TiO 2 with the addition of CuO, occurring at as low as >300 C below the eutectic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
109
1
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(132 citation statements)
references
References 65 publications
(52 reference statements)
6
109
1
16
Order By: Relevance
“…on electric‐field assisted treatments (i. e. flash sintering) showed that the application of a voltage and current to a ceramic specimen during heating promoted stabilization and consolidation at furnace temperatures far below the conventional ones and within few seconds/minutes. The reason for such a rapid process is principally ascribed to a local overheating of the material via Joule effect . Hence, it is evident that the electric properties of the ceramics exert a remarkable role on the treatment conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…on electric‐field assisted treatments (i. e. flash sintering) showed that the application of a voltage and current to a ceramic specimen during heating promoted stabilization and consolidation at furnace temperatures far below the conventional ones and within few seconds/minutes. The reason for such a rapid process is principally ascribed to a local overheating of the material via Joule effect . Hence, it is evident that the electric properties of the ceramics exert a remarkable role on the treatment conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for such a rapid process is principally ascribed to a local overheating of the material via Joule effect. [11,12] Hence, it is evident that the electric properties of the ceramics exert a remarkable role on the treatment conditions. Insulating materials such as SrTiO 3 consolidate at furnace temperatures as high as 1000°C, [13] whereas highly conductive systems like La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3 well below 100°C.…”
mentioning
confidence: 99%
“…Some field/current‐induced effects are claimed by some authors to explain rapid sintering in 3YSZ, magnesia silicate glass‐containing alumina, and B 4 C . In other papers, it is suggested that the enhanced densification of 3YSZ and ZnO upon flash sintering shall be accounted for by an extremely high heating rate associated to the Joule effect; such phenomenon was also associated to two distinct effects: (i) the rapid heating rate in crystalline ceramics often retarded grain coalescence with respect to densification thus allowing a fast densification of nanometric, highly sinterable powder; (ii) the grain‐boundary structure obtained in a very rapid sintering process may differ from that at the equilibrium and may be characterized by unexpectedly high diffusion coefficients . On the other hand, other authors suggested that the field application accelerates sintering by promoting the nucleation of lattice defects, like Frenkel pairs, or by inducing grain‐boundary overheating .…”
Section: Resultsmentioning
confidence: 99%
“…In order to explain the differences between flash‐sintered and fast‐fired samples, we can propose two possible physical models for the specific ceramic system, the former based on conventional theories and Joule heating, and the latter on the activation of field/current‐induced phenomena. We want to point out that the two mechanisms are not applicable to crystalline ceramics like ZnO or 3YSZ whose densification upon flash sintering was suggested to be very similar to that achievable by a rapid heating without electric field and current …”
Section: Resultsmentioning
confidence: 99%
“…Others, have shown that the power surge can be explained satisfactorily as thermal runaway resulting from the negative temperature coefficient of resistivity of most ceramics 14)18) whilst comparison with the sintering of powder compacts rapidly heated without an electric field suggests that the high densification rate may be at least in part a consequence of the fast heating in flash sintering. 19), 20) Further progress requires a better understanding of the conditions during flash sintering. This is a complex and dynamic process with transient temperatures, temperature gradients and constantly changing specimen characteristics (electrical resistivity, thermal conductivity, emissivity, dimensions) as sintering removes porosity and densifies the specimen.…”
Section: Introductionmentioning
confidence: 99%